Nomenclatural changes in some sea cucumbers with the erection of a new genus and description of a Thyone ?juvenile (?n. sp.) from the Gulf of California (Echinodermata:Holothuroidea:Dendrochirotida) - Thandar, Ahmed S. (Zootaxa, 2021)
This paper includes several nomenclatural changes in dendrochirotid holothuroids, mostly based on materials from the USNM. These include the erection of a new genus Pseudostolus for two Indo-Pacific Stolus species [(S. kilberti Rajpal & Thandar, 1999 and S. rapax Koehler & Vaney (1908)], re-assignment of Havelockia uniannulatus (Sluiter, 1914), Thyone pseudofusus Deichmann 1930, T. parafusus Deichmann, 1941 and T. axiologa H.L. Clark, 1938, to the genus Stolus, and re-assignment of Havelockia nozawai (Mitsukuri, 1912) and Thyone adinopoda Pawson & Miller, 1981 to the genus Sclerothyone Thandar, 1989. In addition, a lectotype is designated for (T. vilis Sluiter, 1901), based on the study of type material at the ZMUA. The Caribbean Stolus cognatus is also described and commented on and a single, perhaps juvenile specimen from the Gulf of California is described as Thyone ? n. sp.